Improve Student's Learning Using Media for Understanding and Interest in Pythagorean Theorem Learning - Imam Setiadi Putra (Universitas Islam Lamongan, 2020)
This study focuses on the use of mathematics learning media in improving the students' defense and interest in learning pythagoras theorem. Research subjects taken in one school in Bima City West Nusa Tenggara Indonesia. Research sample were taken randomly/ randomly to follow the learning by using manipulative media. Learning media designed in the study there are two, namely ICT and Non ICT media. ICT media contains about instructional materials, quiz, video and educative games, while in non ICT media bearing on the proof of pythagoras theorem. The results of this study indicate that the use of learning media can improve students' understanding and interest in learning mathematics, it is shown by an increase in the average result of questionnaire interest in learning mathematics students from before the process of learning using media that is equal to 60.27 with after using media-based ie amounted to 87.07. In addition, the results of this study indicate that there is influence of the use of learning media to improve students' understanding on learning pythagoras theorem.